New frontiers in peptide catalysis : multicatalysis, challenging reactions, and the importance of dispersion interactions - Wende, Raffael Christoph; Justus Liebig University Giessen (My University, 2016)
The first part of this thesis is a Critical Review on multicatalysis that is used as a general introduction to this rapidly growing field of research. We define the different types of one-pot reactions employing multiple catalysts, introduce the concept of retrocatalysis and discuss the significant advantages and potential problems associated with multicatalysis. Reactions using combinations of secondary amines, N-heterocyclic carbenes and thiourea catalysts, amongst others, are presented. Finally, we introduce our previous achievements in multicatalysis and disclose the development of the first peptidic multicatalyst.From a library of various peptides Boc-L-Pmh-AGly-L-Cha-L-Phe-OMe was identified as an remarkably efficient catalyst for the kinetic resolution of trans-cycloalkane-1,2-diols. The ee values are typically > 99% (for the remaining diols) corresponding to S-values > 50. Whereas the catalyst is also highly selective for the desymmetrization of meso-alkane-1,2-diols other substrates, e.g., 1,3-diols, provide only low selectivities. The extraordinary chemoselectivity of the peptide is also revealed by competition experiments. Thus, this small tetrapeptide already shows a behavior that may be compared with enzymes. Moreover, computational investigations on complexes of the acylium ion of the catalyst with the fast reacting enantiomer of trans-cyclohexan-1,2-diol were performed. The exceptionally high selectivities are made possible by the interplay of the aminoadamantane carboxylic acid that froms a dynamic binding pocket as well as by attractive dispersion interactions of the cyclohexyl residue with the substrate.A multicatalytic enantioselective oxidative esterification is reported. The combination of TEMPO as oxidation catalyst and p-nitrobenzoic acid as additive allows the oxidation of a variety of aldehydes to their mixed anhydrides. These are enantioselectively transferred onto trans-cycloalkane-1,2-diols with up to 94% ee for the recovered diol and 93% ee for the corresponding acylated derivative. The reaction progress and the formation of the mixed as well as symmetric anhydrides was followed by NMR spectroscopy. The reaction could also be performed with our previously developed multicatalyst instead of the two individual catalysts.In cooperation with Prof. Dr. Wolfgang Schrader a multicatalyst incorporating Pmh and a diacid as catalytic moieties was studied by high-resolution mass spectrometry. The peptide was previously used for a one-pot epoxidation/hydrolysis/kinetic resolution sequence starting from simple alkenes and affording enantiomerically enriched trans-cycloalkane-1,2-diols. Although the selectivities are synthetically useful (64 99% ee for the remaining diol) they can not compete with the selectivities achieved with the corresponding tetrapeptide alone. All important intermediates have been identified and characterized. It was found that the epoxidation step also leads to a partial oxidation of the imidazole moiety and consequently to a reduced catalytic performance of the multicatalyst.We envisaged the development of a multicatalytic reaction sequence for the synthesis of 2-deoxygalactosides. Our approach is based on the partial protection of carbohydrates that may subsequently act as glycosyl donors. We identified Boc-D-Pmh-AGly-L-Val-L-Phe-OMe to be a highly regioselective catalyst in the acetylation of methyl 4,6-O-benzylidene-alpha-D-glucopyranoside. In comparison to simple N-methylimidazole, which mostly leads to the acetylation of the 3-hydroxy group on the substrate (2-OAc/3-OAc/diacetylated: 22:70:8; 93% conversion), the peptide preferentially gives the 2-acetylated product (2-OAc/3-OAc/diacetylated: 85:9:6; > 95% conversion). Thus, this catalyst is not simply enhancing but completely overriding the inherent reactivity of the substrate.The Dakin West reaction is one of the most viable methods for the preparation of alpha-acylamido ketones directly from the corresponding primary alpha-amino acids. Although this reaction was known for decades no enantioselective variant has been reported previously. We found that the complexity of the mechanism of the reaction requires the separation of the two crucial steps: the acetylation of the azlactone intermediate and the final decarboxylation step. Under optimized reaction conditions the Pmh-containing peptide catalysts act as a Lewis base in the first step and as a Brønsted base in a final enantioselective decarboxylative protonation. With the best-working catalyst selectivities with up to 58% ee were achieved with good yields. Two of the obtained products were recrystallized once to achieve up to 84% ee. Importantly, computational investigations further proved the importance of dispersion interactions in the enantioselectivity determining reaction step.
Keywords: ddc:540